A122 CHARACTERIZING A LOST-TO-FOLLOW-UP COHORT AMONGST PATIENTS DIAGNOSED WITH PEDIATRIC ONSET INFLAMMATORY BOWEL DISEASE IN THE PEDIATRIC TO ADULT TRANSFER OF CARE. (1st March 2018) - Bollegala, N; Benchimol, E I; Griffiths, A; Kovacs, A; Steinhart, H; ZHAO, X; Nguyen, G C
Abstract: Background: Pediatric onset inflammatory bowel disease (IBD) is a high-risk phenotype that requires transfer to an adult gastroenterologist at age 18. Under-developed emotional and cognitive skills in the transition-aged population can affect adherence rates, especially during periods of remission. A recent study evaluating patients with pediatric onset IBD requiring transfer of care to an adult gastroenterologist identified a relatively large lost to adult gastroenterology (GI) follow-up (LTF) group. Aims: The purpose of this study was to characterize those patients with pediatric onset IBD who are LTF in the first five years of adult care and identify risk factors for their non-compliance. Methods: This was a population-based retrospective cohort study using health care administrative data from Ontario, Canada. A cohort of patients with pediatric onset IBD was identified and health resource utilization during a 5-year post-transfer period was analyzed. Patients LTF were compared to those patients actively followed by a gastroenterologist in terms of health resource utilization. The primary outcome of this study comprised Emergency Department (ED) utilization. Secondary outcomes included hospitalizations, surgeries, ambulatory visits, endoscopic and radiological investigations. Results: 2043 patients with pediatric onset IBD were identified. 1696 were followed by an adult GI in the post-transfer period. 306 patients were never seen by an adult GI. 41 patients were never seen by any adult health care provider in the post-transfer period. Patients in the loss to follow-up group were significantly younger, more likely to be male, have ulcerative colitis (UC) and reside in an urban environment. Overall, there were no significant differences found in ED use, total ambulatory care visits (aside from the expected drop amongst GI follow-up), hospitalizations, endoscopic procedures or radiological procedures between exposure groups. Multivariable negative binomial logistic regression revealed that the LTF group was less likely to be seen in the ED and admitted to hospital. Conclusions: A relatively large LTF group with pediatric onset IBD was characterized in this study. 5-year follow-up reveals no evidence of increased health resource utilization. More work is needed to further define this population, identify barriers to follow-up and whether outcomes such as quality of life, productivity etc. are affected by their non-compliance. Funding Agencies: CCC